2006
DOI: 10.1159/000090648
|View full text |Cite
|
Sign up to set email alerts
|

Does Inflammatory Linear Verrucous Epidermal Nevus Represent a Segmental Type 1/Type 2 Mosaic of Psoriasis?

Abstract: Background: A 6-year-old girl with a symmetric linear eruption on both of her legs, clinically and histologically resembling inflammatory linear verrucous epidermal nevus (ILVEN) or linear psoriasis (LP), with concomitant psoriasis of the guttata type and a positive family history of psoriasis is presented. The questions as to whether LP actually exists and ILVEN represents a distinct entity are still under debate. Objective and Methods: The recent literature concerning case reports of ILVEN and LP is reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 62 publications
(51 reference statements)
0
37
0
Order By: Relevance
“…To describe the coexistence of segmental and nonsegmental lesions of a polygenic disorder, some authors have proposed the terms ''type 2 mosaicism'' 6,21,55 or ''type 2 segmental mosaicism,'' 20 and, even in a case of isolated linear lichen planus, a ''type 2 LOH pattern'' has been assumed. 33 Such terminology, however, reflects a misunderstanding.…”
Section: Discussionmentioning
confidence: 99%
“…To describe the coexistence of segmental and nonsegmental lesions of a polygenic disorder, some authors have proposed the terms ''type 2 mosaicism'' 6,21,55 or ''type 2 segmental mosaicism,'' 20 and, even in a case of isolated linear lichen planus, a ''type 2 LOH pattern'' has been assumed. 33 Such terminology, however, reflects a misunderstanding.…”
Section: Discussionmentioning
confidence: 99%
“…This debate is nicely illustrated in a recent issue of Dermatology, where Thomas Hofer hypothesized that ILVEN might represent a mosaic form of psoriasis [1] whereas Rudolf Happle suggested that ILVEN and linear psoriasis are different entities [2] . We report …”
Section: Abstract Epidermal Naevus ؒ Inflammatory Linear Verrucous Ementioning
confidence: 99%
“…In this issue, Thomas Hofer [1] presents an unusual case of linear psoriasis superimposed on psoriasis vulgaris. The author is discussing the nosological problem of whether ILVEN and linear psoriasis are different entities.…”
mentioning
confidence: 99%
“…For example, the case presented by Hofer [1] fulfi ls all of the clinical criteria of linear psoriasis [3] . A grandfather of the patient had had psoriasis vulgaris since his youth.…”
mentioning
confidence: 99%
See 1 more Smart Citation